Estrogen deprivation aggravates intracellular calcium dyshomeostasis in the heart of obese-insulin resistant rats - Siripong Palee (2018)
© 2018 Wiley Periodicals, Inc. The incidence of cardiovascular disease and metabolic syndrome increases after the onset of menopause, giving evidence for the vital role of estrogen. Intracellular calcium [Ca2+]i regulation plays an important role in the maintenance of left ventricular (LV) contractile function. Although either estrogen deprivation or obesity has been shown to strongly affect the metabolic status and LV function, the effects of estrogen deprivation on the cardiometabolic status and cardiac [Ca 2+]i regulation in the obese-insulin resistant condition have never been investigated. Our hypothesis was that estrogen deprivation aggravates LV dysfunction through the increased impairment of [Ca 2+]i homeostasis in obese-insulin resistant rats. Female rats were fed on either a high-fat (HFD, 59.28% fat) or normal (ND, 19.77% fat) diet for 13 weeks. Then, rats were divided into sham (HFS and NDS) operated or ovariectomized (HFO and NDO) groups. Six weeks after surgery, metabolic status, LV function and incidence of [Ca 2+]i transients were determined. NDO, HFS, and HFO rats had evidence of obese-insulin resistance indicated by increased body weight with hyperinsulinemia and euglycemia. Although NDO, HFS, and HFO rats had markedly reduced %LV fractional shortening, E/A ratio and decreased [Ca 2+]i transient amplitude and decay rate, HFO rats had the most severe impairments. These findings indicate that estrogen deprivation had a strong impact on abnormal LV function through [Ca 2+]i regulation. In addition, evidence was found that in obese-insulin resistant rats, estrogen deprivation severely aggravates LV dysfunction via increased impairment of [Ca 2+]i homeostasis.